2022
DOI: 10.4236/jcdsa.2022.124014
|View full text |Cite
|
Sign up to set email alerts
|

Triple Wavelength and 810 nm Diode Lasers for Hair Removal: A Clinical and <i>in Silico</i> Comparative Study on Indian Skin

Abstract: In laser hair removal treatments on dark skin, the high concentration of melanin in the skin competes with the melanin in the hair. During standard laser procedures, with wavelengths of 755 nm or 810 nm, a high level of laser light absorption by melanin in the skin is observed. Therefore, to avoid side effects, lower fluence values are used, which further reduces hair-removal efficacy. To improve results, 810 nm diode lasers operating in dynamic mode, with high frequency and multiple passes, are typically used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(11 citation statements)
references
References 12 publications
1
10
0
Order By: Relevance
“…This outcome suggests that, through the use of the triple wavelength diode laser, patients with darker skin types could achieve similar results to those achieved in subjects with lighter skin. 20 Indeed, the recent study by Pall et al, resulted in 27% greater hair reduction in Indian patients with a triple wavelength (810, 940, and 1060 nm) laser compared with a standard 810 nm diode laser. 20 Other reports in the literature demonstrated that the high-power 4000 W Primelase triple wavelength diode laser was shown to be effective and satisfactory on darker skin types, while also being safe and comfortable for participants.…”
Section: Materials S and Me Thodsmentioning
confidence: 98%
See 4 more Smart Citations
“…This outcome suggests that, through the use of the triple wavelength diode laser, patients with darker skin types could achieve similar results to those achieved in subjects with lighter skin. 20 Indeed, the recent study by Pall et al, resulted in 27% greater hair reduction in Indian patients with a triple wavelength (810, 940, and 1060 nm) laser compared with a standard 810 nm diode laser. 20 Other reports in the literature demonstrated that the high-power 4000 W Primelase triple wavelength diode laser was shown to be effective and satisfactory on darker skin types, while also being safe and comfortable for participants.…”
Section: Materials S and Me Thodsmentioning
confidence: 98%
“…20 Indeed, the recent study by Pall et al, resulted in 27% greater hair reduction in Indian patients with a triple wavelength (810, 940, and 1060 nm) laser compared with a standard 810 nm diode laser. 20 Other reports in the literature demonstrated that the high-power 4000 W Primelase triple wavelength diode laser was shown to be effective and satisfactory on darker skin types, while also being safe and comfortable for participants. 5,17,18,20 Fajardo-Urdiales et al…”
Section: Materials S and Me Thodsmentioning
confidence: 98%
See 3 more Smart Citations